Shielding performance of T-shaped periodic barrier for surface waves in transversely isotropic soil. (November 2022) - Ji, De-Xin; Yu, Gui-Lan
Aiming at the vibration isolation in transversely isotropic soil, a T-shaped partially embedded periodic barrier for surface waves is proposed, and its shielding performance is explored by using finite element method combined with Bloch-Floquet theory. Seven independent dimensionless material parameters are derived and their influences on band gaps are discussed numerically. The results show that the band gaps exhibit strong sensitivity to the three parameters out of seven, and the band gaps are far wider in transversely isotropic soils than that in the isotropic. The mass density ratio and the shear modulus ratio of the barrier to the soil, as well as the length ratio of the barrier above the ground to that below, can be used to adjust band gaps effectively to meet the shielding requirements for different frequency ranges under different anisotropic soils. As a case of study, the El Centro seismic wave is considered and found that it can be considerably attenuated by the designed periodic barrier.